130 Years of Medicine in Hong Kong From the College of Medicine for Chinese to the Li Ka Shing Faculty of Medicine - Ching, Frank (Springer Singapore, 2018)
This book reviews the medical history of Hong Kong, beginning with its birth as a British colony. It introduces the origins of Hong Kong's medical education, which began in 1887 when the London Missionary Society set up the Hong Kong College of Medicine for Chinese. When the University of Hong Kong was established in 1911, the College became its medical faculty. The faculty has gained distinction over the years for innovative surgical techniques, for discovering the SARS virus and for its contribution to advances in medical and health sciences. This book is meant for general readers as well as medical practitioners. It is a work for anyone interested in Hong Kong or in medical education.